Effect of ethyl pyruvate on human esophageal squamous cell carcinoma transplanted tumors in nude mice: Ethyl pyruvate impact on esophageal cancer in mice - Liang, Xuyang; Wen, Jing; Xu, Jing; Zhang, Zhimei; Zhang, Shuxian; Wang, Lu (Cellular and Molecular Biology, 2024)
The objective of this study was to investigate the impact of ethyl pyruvate (EP), an HMGB1 inhibitor, on ESCC cells both in vitro and in vivo. The viability of ESCC cells was assessed using the MTT method to evaluate the correlation between EP and cell viability. A scratch test was used to investigate the relationship between EP and cell migration and invasion. The effects of EP on tumor growth and survival in cancerous nude mice were examined using a tumor formation model. Immunohistochemical staining was performed to evaluate the expression levels of HMGB1, TLR4, and MyD88 in tumor tissues. EP, an anti-HMGB1 inhibitor, inhibited ESCC cell proliferation and metastasis in vitro and in vivo. Furthermore, compared with the control treatment, EP improved the activity, diet, and drinking behaviour of nude mice; inhibited tumour growth; and led to lower protein expression levels of HMGB1, TLR4, and MyD88. EP has the potential to regulate the HMGB1/TLR4-MyD88 signaling pathway, thereby inhibiting the proliferation and metastasis of ESCC, suppressing tumor growth, improving quality of life, and serving as an effective drug for ESCC treatment.